PENGARUH KOMUNIKASI PEMASARAN, HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada CV. Pacific Andre Anton di Situbondo) - Novia, Rozana Putri; Arief, Mohammad Yahya; Syahputra, Hendra (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Increasing business competition certainly requires the right marketing strategy, so that business can run effectively and efficiently. Offering high-quality products and communicating with consumers appropriately are two examples of consumer behavior in the target market that business people must know. The purpose of this study was to analyze the effect of marketing communication, price, and product quality on consumer satisfaction through purchasing decisions. This research is explanatory research. The population in this study were consumers of CV. Pacific Andre Anton in Situbondo. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test with the Smart PLS 3.0 application, show that marketing communication has a significant effect on purchasing decisions. Price also has a significant effect on purchasing decisions, then product quality has no significant effect on purchasing decisions, marketing communication has a significant effect on customer satisfaction, price does not have a significant effect on customer satisfaction, product quality has no significant effect on customer satisfaction, and purchasing decisions have a significant effect on customer satisfaction. The results of the indirect effect hypothesis test show that the variable marketing communication on customer satisfaction through purchasing decisions has a significant positive effect, price on customer satisfaction through purchasing decisions has a positive but insignificant effect, product quality on customer satisfaction through purchasing decisions has a negative but insignificant effect.